Peningkatan Keterampilan Berbicara Peserta Didik Menggunakan Model Kooperatif Tipe Team Games Tournament (TGT) di Kelas IV SDN 04 Buo Kabupaten Tanah Datar - Hafifa, Hafifa; Muhammadi, Muhammadi (TSAQOFAH, 2025)
The low speaking skills of elementary school students are often attributed to the lack of learning activities that encourage active participation, as the learning process remains largely teacher-centered. This condition leads to students struggling to formulate words and speak fluently in front of the class. This study aims to describe the improvement of speaking skills through the implementation of the cooperative learning model, Team Games Tournament (TGT) type. The research employed Classroom Action Research (CAR) with both qualitative and quantitative approaches, conducted over two cycles comprising planning, implementation, observation, and reflection stages. The subjects were a teacher and 18 fourth-grade students at SDN 04 Buo. Data were collected through observation and speaking skill tests. The results showed improvement across all aspects: the instructional module increased from 87.49% (good category) to 93.75% (very good category); teacher and student performance improved from 87.49% to 95.83%; and students’ speaking skills rose from 79.89% to 92.11%. These findings demonstrate that the Team Games Tournament model is effective in enhancing students’ speaking abilities through more interactive and competitive learning. The implication is that this model can serve as an alternative strategy for teaching Bahasa Indonesia, focusing on actively and enjoyably strengthening language skills.